1988
DOI: 10.1139/f88-059
|View full text |Cite
|
Sign up to set email alerts
|

Modification and Assessment of an Index of Biotic Integrity to Quantify Stream Quality in Southern Ontario

Abstract: A multivariate measure of stream quality, the Index of Biotic Integrity (IBI), was adapted to southern Ontario and calibrated to watershed land use on a variety of spatial scales. The fish fauna at 209 stream locations on 10 watersheds near Toronto, Ontario, was sampled with a backpack electrofisher in the summers of 1984 and 1985 to provide biological information for the IBI. Watershed urbanization, forest cover, and riparian forest were measured from 1:50,000 scale topographic maps and related to IBI estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
192
3
4

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(212 citation statements)
references
References 0 publications
11
192
3
4
Order By: Relevance
“…Results from MRPP showed that overall, urban streams possessed significantly different assemblages than reference streams (A = 0.169; P < 0.001). dIscussIon clear differences existed between species assem blages in urban areas and those in relatively unmodified (reference) areas in the Auckland region, and these differences agree with similar studies conducted elsewhere (e.g., Steedman 1988;Schueler & Galli 1992;wang et al 1997;boet et al 1999).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Results from MRPP showed that overall, urban streams possessed significantly different assemblages than reference streams (A = 0.169; P < 0.001). dIscussIon clear differences existed between species assem blages in urban areas and those in relatively unmodified (reference) areas in the Auckland region, and these differences agree with similar studies conducted elsewhere (e.g., Steedman 1988;Schueler & Galli 1992;wang et al 1997;boet et al 1999).…”
Section: Resultssupporting
confidence: 88%
“…Especially noted is the low incidence of research involving freshwater fish communities. Those studies that have used fish as focal organisms have found declines in freshwater fish species richness (Klein 1979;boet et al 1999), species diversity (Klein 1979;Schueler & Galli 1992), fish Index of biotic integrity (ibi) (Steedman 1988;wang et al 1997), and increases in occurrence of invasive fish species (Boet et al 1999). These studies are New Zealand Journal of Marine and Freshwater Research, 2009, Vol.…”
Section: Introductionmentioning
confidence: 99%
“…Except for the work of Donohue, McGarrigle & Mills, (2006) in Ireland, we are not aware, within Europe, of models linking human activities (evaluated through land cover) to ecological status at a large or even a regional scale. In one of the pioneer works, Steedman, (1988) demonstrated positive relationships between the condition of the fish community and both the percentage of forest in the basin and the proportion of channel with riparian forest, and a strong negative relationship with urbanization in the catchment. He also emphasized the need for a more detailed evaluation of agricultural land use and streamside vegetation to improve predictive models.…”
Section: Introductionmentioning
confidence: 99%
“…D'un autre côté, il a été rapporté des cas de pollution subléthale où la biodiversité est plus élevée qu'en absence de pollution (Connell 1978). De même, Steedman (1988) constate des abondances plus élevées dans les rivières enrichies en matière organique ou réchauffées. La situation actuelle de la recolonisation est celle d'une forte abondance assurée par quelques espèces.…”
Section: Abondanceunclassified